Method for determining final annealing conditions of grain-oriented electromagnetic steel sheets and method for manufacturing grain-oriented electromagnetic steel sheets using the same
By adjusting control items such as the atmosphere switching temperature according to the enrichment state of the internal oxide film during the final annealing process of grain-oriented electrical steel sheets, the problem of uneven base film characteristics in the length and width directions of the coil is solved, the yield and product quality are improved, and manufacturing costs are reduced.
Patent Information
- Application Number
- CN202280017476.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-03
- Filing Date
- 2022-03-03
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2042-03-03
AI Technical Summary
In the prior art, during the final annealing process of grain-oriented electromagnetic steel sheets, there is a problem of uneven base film properties in the length and width directions of the coil, resulting in reduced yield and increased manufacturing costs. In particular, the base film properties are prone to deterioration in the upper and lower parts and the inner and outer coils of the coil.
By dividing the coil into multiple areas along the length and width, the enriched components of the internal oxide film are monitored, and the control items of the final annealing, such as the atmosphere switching temperature and heating rate, are adjusted using the optimal function and the allowable value range to ensure the uniformity and excellent characteristics of the base film.
The stability of the base film properties in the coil is improved, the yield and product quality are significantly improved, and the manufacturing cost is reduced.
Smart Images

Figure CN116917508B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for determining the final annealing conditions for a grain-oriented electrical steel sheet, and more specifically, to a method for determining the final annealing conditions for a grain-oriented electrical steel sheet for uniformly coating the coil with a base film mainly composed of forsterite, spinel, or the like in the longitudinal and width directions to obtain a high-quality grain-oriented electrical steel sheet with a high yield.
[0002] Furthermore, the present invention relates to a method for producing a grain-oriented electrical steel sheet using the above-mentioned method for determining the finish annealing conditions. Background Art
[0003] Magnetic steel sheets are soft magnetic materials widely used as materials for transformer and motor cores. Grain-oriented magnetic steel sheets, in particular, are primarily used for large transformer cores because their crystals are highly concentrated in the {110}<001> orientation known as the Goss orientation, resulting in excellent magnetic properties.
[0004] These grain-oriented electrical steel sheets are typically produced by hot-rolling a steel billet containing a large amount of Si, followed by cold rolling. After decarburization annealing, an annealing separator primarily composed of MgO is applied, and a final annealing step is performed. The high degree of Goss orientation is achieved by maintaining the steel at a high temperature of 800°C or higher for a long period of time during the final annealing, which causes secondary recrystallization.
[0005] In the above-mentioned final annealing, after secondary recrystallization occurs, the steel is heated to a high temperature of about 1200°C to remove impurities in the steel, and the internal oxide film generated in the decarburization annealing step reacts with the annealing separator mainly composed of MgO to form a base film mainly composed of forsterite.
[0006] This base film has the effect of applying tension to the steel sheet to reduce iron loss, and also functions as a binder for the insulating film applied later, thereby contributing to improvements in the insulation and corrosion resistance of the steel sheet.
[0007] The internal oxide film formed during decarburization annealing is subject to complex oxidation behavior, influenced by residual oxides from previous processes, the texture of the steel sheet surface, the fact that oxidation proceeds through non-equilibrium reactions, and the simultaneous occurrence of decarburization. Furthermore, since this decarburization annealing is also a high-dew-point annealing, maintaining a uniform furnace atmosphere is extremely difficult, leading to the problem of uneven oxidation between the surface and back of the steel sheet, and between the ends and center of the coil.
[0008] On the other hand, in final annealing, the coiled steel sheet is placed in an upright position (up-end) with the coil axis vertical in the final annealing furnace and maintained at high temperature for a long time. This causes temperature unevenness within the coil. This temperature unevenness causes variations in film properties in the longitudinal direction of the coil and the width direction of the sheet.
[0009] In particular, the outer edges of the upper and lower ends of the upright coils are overheated during the final annealing, causing problems such as peeling of the base film or point defects. This can easily reduce product yield.
[0010] To address these issues, various techniques have been proposed to improve magnetic and film properties by designing final annealing conditions. For example, Patent Document 1 proposes a method for promoting steel sheet purification by repeatedly increasing and decreasing furnace pressure within a specific final annealing temperature range.
[0011] Patent Document 2 proposes a method for improving coil shape by using MgO with limited repose angle and stacking height as an annealing separator and optimizing the winding tension of the coil after the annealing separator is applied.
[0012] Patent Document 3 proposes a method for suppressing deterioration of magnetic properties and film properties by using a sealing material having a specific particle size at the lower end of an inner cover during final annealing in a rotary hearth box furnace.
[0013] Patent Documents 4 and 5 propose methods of increasing the flow rate of the atmospheric gas during the final annealing of a steel sheet to which Bi is added, thereby increasing the tension applied to the base film.
[0014] Prior art literature
[0015] Patent Literature
[0016] Patent Document 1: Japanese Patent Application Laid-Open No. 2000-239736
[0017] Patent Document 2: Japanese Patent Application Laid-Open No. 2001-303137
[0018] Patent Document 3: Japanese Patent Application Laid-Open No. 08-209248
[0019] Patent Document 4: Japanese Patent Application Laid-Open No. 09-003541
[0020] Patent Document 5: Japanese Patent Application Laid-Open No. 09-111346 Summary of the Invention
[0021] However, in the method described in Patent Document 1, if a negative pressure is locally generated in the annealing furnace when the pressure is reduced, there is a risk that atmospheric air may intrude into the furnace, causing abnormal combustion of the atmosphere gas and deterioration of film properties.
[0022] In addition, the method described in Patent Document 2 improves the coil shape to some extent, but the coil is tightly wound due to the increased winding tension, which deteriorates the flow of atmospheric gas between coil layers and may lead to deterioration of magnetic properties and film properties.
[0023] The method of limiting the particle size of the sealing material to a specific size as described in Patent Document 3 and the methods of increasing the gas flow rate as described in Patent Documents 4 and 5 have a limit to the improvement of magnetic properties and film properties, and there is a problem that sufficient improvement effects cannot be obtained.
[0024] As described above, by applying the technologies described in these patent documents, film properties and magnetic properties have indeed been gradually improved.
[0025] However, this method still fails to fully meet the stringent quality requirements of recent years. In particular, poor base film properties that occur during final annealing at the upper and lower portions of the coil (at both ends in the coil width direction) and at the inner and outer coils (at both ends in the coil length direction) must be cut off before shipment. This reduces yield and increases the manufacturing cost of grain-oriented electrical steel sheets.
[0026] The present invention has been made in view of the above-mentioned problems existing in the prior art, and its object is to provide a method for determining the final annealing conditions for producing high-quality grain-oriented electrical steel sheet that can meet the above-mentioned strict quality requirements in recent years by imparting good coating properties even to areas where the properties of the base coating, such as forsterite, are easily deteriorated, such as the upper and lower parts of the coil and the inner and outer coils during final annealing, and a manufacturing method using the same.
[0027] The present inventors conducted intensive research to solve the above problems and found that:
[0028] The concentrations of O, Si, Al, Mn, and P in the decarburized annealed sheet, the state of the enriched components (intensity ratio) of the internal oxide film containing the oxide-forming components Fe2SiO4, SiO2, and FeO, and the final annealing conditions vary depending on the position in the coil, which is the cause of the reduction in yield.
[0029] However, it is difficult to reduce the variation within the coil by adjusting the state of the enriched components of the internal oxide film and the conditions of the final annealing in existing manufacturing equipment.
[0030] On the other hand, if a good base film can be obtained by adjusting the conditions of the final annealing according to the state of the enriched components of the internal oxide film, degradation of the base film properties within the coil can be reduced.
[0031] Based on the above findings, the present inventors conducted further studies and constructed a control model for optimizing yield based on the state of the enriched components of the internal oxide film and the in-coil variations in the conditions of the final annealing, thereby completing the present invention.
[0032] That is, the present invention is as follows.
[0033] 1. A method for determining final annealing conditions for a grain-oriented electrical steel sheet, wherein a steel billet for the grain-oriented electrical steel sheet is hot-rolled, then subjected to one cold rolling step or two or more cold rolling steps with intermediate annealing, further subjected to a decarburization annealing step also serving as a primary recrystallization annealing step, coated with an annealing separator, and wound into a coil, followed by final annealing to form a base film, and then subjected to flattening annealing to produce a product sheet.
[0034] When determining the conditions for the above-mentioned final annealing, perform the following operations:
[0035] 1) when the steel sheet after decarburization annealing is divided into a plurality of regions in the longitudinal direction and the width direction, information on the enrichment component index (M) in the internal oxide film of the steel sheet after decarburization annealing is obtained for each of the regions;
[0036] 2) before determining the final annealing conditions, deriving an optimal function f(M) of the final annealing control item with respect to the enrichment component index (M) based on an evaluation result of the influence of the final annealing control item on the properties of the base film for the enrichment component;
[0037] 3) obtaining information on the entire steel plate regarding the distribution of the control item for each of the regions with respect to a plurality of candidate values for the setting value (H) of the control item for the final annealing,
[0038] 4) Determine whether the distribution of the control items in each of the above-mentioned areas is within the range of the prescribed allowable value (±δ) relative to the above-mentioned f(M), and select the setting value (H) of the control item with the largest total area of the area within the range of the above-mentioned allowable value from the above-mentioned multiple candidate values.
[0039] 2. The method for determining the final annealing conditions of a grain-oriented electrical steel sheet according to item 1 above, wherein the enrichment component index (M) is set to any one or more of the following: O concentration, Si concentration, Al concentration, Mn concentration, P concentration, Fe2SiO4 intensity ratio, SiO2 intensity ratio, and FeO intensity ratio on the steel sheet surface.
[0040] 3. The method for determining the final annealing conditions for a grain-oriented electrical steel sheet according to 1 or 2 above, wherein the control parameters for the final annealing are any one or more of the heating rate between 950°C and 1100°C, the atmosphere switching temperature, the homogenization heat treatment time, and the homogenization heat treatment temperature during the final annealing.
[0041] 4. A method for producing a grain-oriented electrical steel sheet, comprising using the method for determining the final annealing conditions according to any one of 1 to 3 above.
[0042] The present invention enables stable production of grain-oriented electrical steel sheets with excellent base coating properties, regardless of coil length or width. Consequently, the present invention significantly contributes to improved product quality, increased yield, and reduced manufacturing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The graph plots the distribution of P intensity across the entire length and width of the coil.
[0044] Figure 2 This is a graph showing the relationship between the atmosphere switching temperature and the film characteristics with respect to the P strength of the steel sheet.
[0045] Figure 3 This is a diagram simulating the temperature distribution of a representative point at 830°C during the final annealing of a coil.
[0046] Figure 4 The graph plots the difference between the optimal atmosphere switching temperature calculated based on the P intensity assumption across the entire length and width of the coil and the estimated temperature calculated for each coil position at atmosphere switching temperatures of 700°C, 800°C, and 900°C. DETAILED DESCRIPTION
[0047] First, the experiments for developing the present invention will be described.
[0048] Experiment 1
[0049] A steel containing 0.06 mass% C, 3.3 mass% Si, 0.07 mass% Mn, 0.016 mass% Al, and 0.003 mass% S, with the remainder consisting of Fe and inevitable impurities, was smelted and formed into a steel billet (slab) by a continuous casting method. The slab was then heated to 1380°C and hot-rolled to form a hot-rolled plate with a thickness of 2.2 mm. The hot-rolled plate was annealed at 1000°C for 60 seconds, followed by a primary cold rolling to form an intermediate plate with a thickness of 1.8 mm. After an intermediate annealing at 1100°C for 80 seconds, a secondary cold rolling was performed to form a cold-rolled plate with a final thickness of 0.23 mm.
[0050] Next, the cold-rolled sheet was subjected to a decarburization annealing process, which also served as a primary recrystallization annealing, by heating it in a horizontal continuous annealing furnace at a heating rate of 100°C / s between 500°C and 700°C. After further heating to 860°C, the temperature was held at that temperature for 140 seconds. During this decarburization annealing, an atmosphere gas with a vol% ratio of H2:N2 = 60:40 was supplied from above and below the annealing furnace.
[0051] For the steel plate after decarburization annealing, the intensity of P, which is one of the enriched components in the internal oxide film, is analyzed online using a fluorescent X-ray device before being wound into a coil (this intensity is the intensity of the X-ray and is proportional to the concentration (or enrichment amount). Therefore, in the present invention, intensity and concentration (enrichment amount) can be understood as synonymous). At this time, the fluorescent X-ray device uses an energy dispersion type and is performed under the conditions of voltage: 50kV and current: 10mA. The P intensity is analyzed every 50mm in the width direction of the plate and every 50m in the length direction to produce a distribution diagram of the P intensity of the X-ray. The diagram is shown in Figure 1 It should be noted that the total length of the coil is 5000m and the total width is 1000mm.
[0052] The figure shows that the X-ray P intensity varies slowly within the range of 1.4 to 2.6 kcps in both the longitudinal and width directions of the steel sheet. This is believed to be due to the influence of the flow of the atmospheric gas in the annealing furnace and the surface properties of the steel sheet in the previous process.
[0053] The cold-rolled steel sheet after decarburization annealing was coated with an annealing separator prepared by slurrying MgO-based powder containing 5 mass% titanium oxide and 0.1 mass% sodium borate in water. The slurry was dried and then wound into a coil for final annealing.
[0054] Next, final annealing was performed by varying the atmosphere switching temperature, one of the control items in the final annealing, to form a base film on the steel sheet surface. The uniformity of the base film in the product sheet after final annealing was evaluated. The results are summarized and shown in terms of the relationship between the intensity of P in the internal oxide film of the steel sheet after decarburization annealing and the atmosphere switching temperature. Figure 2 Here, regarding the uniformity of the base film, a film having a uniform appearance with a constant thickness was evaluated as "uniform", and a film having a portion thinner than the surrounding portion was evaluated as "partial defect".
[0055] The above experimental results show that a good film can be obtained if the atmosphere switching temperature, which is one of the control items in the final annealing, is controlled within an appropriate range according to the P intensity.
[0056] This means that the higher the P concentration and the lower the atmosphere switching temperature, the easier it is to form a base film. Therefore, if the P concentration is high and the atmosphere switching temperature is low, base film formation is excessively accelerated, resulting in localized excess base film, which is prone to detachment and deteriorates the properties of the base film. On the other hand, the inventors believe that if the P concentration is low and the atmosphere switching temperature is high, base film formation is delayed, resulting in a thinner base film overall, which also deteriorates the base film.
[0057] Depend on Figure 2 It can be seen that the relationship between the P intensity of the internal oxide film and the atmosphere switching temperature indicates that the region that ensures uniformity of the base film lies between 1080-100×(P intensity)-180°C and 1080-100×(P intensity)+180°C. Specifically, it was found that the optimal value of the atmosphere switching temperature for the final anneal (also referred to as the optimal value in this invention) can be calculated based on 1080-100×(P intensity) (also referred to as the optimal function f(M) in this invention), and that a good base film is formed if the difference (also referred to as the tolerance value δ in this invention) between this value and the actual atmosphere switching temperature (also referred to as the set value (H) in this invention) given by the representative point of the final annealing H2 switching temperature described later is within 180°C. Therefore, by adjusting the atmosphere (e.g., H2) switching temperature for the final annealing according to the P intensity of the internal oxide film, uniformity of the base film can be ensured.
[0058] The representative point is a measurement location of a thermocouple attached to the hearth at a position in contact with the lower portion of the coil.
[0059] In addition, the set value (H) mentioned in the present invention can use the temperature actually reached by the steel plate, such as the actual atmosphere switching temperature mentioned above as an example, that is, the output value, but it can also be a so-called input value such as the command temperature (set temperature) and the value of the actual control item such as the fuel gas amount, the input power amount, etc. As long as it is unified in one simulation, any of the above values can be applied to the present invention.
[0060] Next, to simulate the temperature history of the final annealing, a separate coil coated with an annealing separator was used. Multiple thermocouples were attached to the coil for final annealing. Based on the temperature data at this time, the temperature inside the coil was simulated using the finite element method.
[0061] The final annealing in this process involves heating between room temperature and 950°C at a heating rate of 25°C / h in an N2 atmosphere, and heating between 950°C and 1100°C at a heating rate of 20°C / h in an H2 atmosphere to complete secondary recrystallization. Subsequently, the steel is heated between 1100°C and 1200°C in an H2 atmosphere at a heating rate of 10°C / h, followed by a purification treatment by holding the temperature at 1200°C for 10 hours. The temperatures listed above and in the following annealing processes are based on the temperature of a thermocouple attached to the lower hearth in contact with the coil as a representative control temperature (representative point temperature).
[0062] In this heating mode, the temperature distribution of the entire steel sheet in the coil when the temperature of the representative point during annealing is 830°C was simulated by the finite element method. The results are shown in FIG. Figure 3 The figure also shows the coils at 50mm intervals in the width direction and 50m intervals in the length direction. Note that the total length of the coil is 5000m and the total width is 1000mm.
[0063] Depend on Figure 3 The results show that the temperature is lowest near the representative point slightly below the center of the plate width of the coiled portion, and the difference between the highest and lowest temperatures is about 200°C.
[0064] Based on this result, the experiment was further carried out according to the following steps.
[0065] That is, using the above formula of 1080-100×(P intensity), the appropriate temperature for switching the atmosphere from N2 to H2 is calculated based on the P intensity at each coil position. In addition, the simulated temperature of each coil position at each time of the atmosphere switching temperature of 700, 800, and 900°C as the setting candidate values (h0, h1, h2) is calculated. Then, the difference Δ between the above-calculated appropriate temperature for switching from N2 to H2 and the simulated temperature of each coil position is plotted. The results are shown in Figure 4 .
[0066] Depend on Figure 4 It can be seen that when the atmosphere switching temperature is set to 700°C, regions where the absolute value of Δ exceeds 180°C (the aforementioned δ) are widely observed across the entire steel sheet on the coiling hearth side of the coil. Meanwhile, at 900°C, regions where the absolute value of Δ exceeds 180°C (the aforementioned δ) occur in the outermost and innermost coils. In contrast, at the intermediate temperature of 800°C, 99.8% of the steel sheet area falls within the range of 180°C (the aforementioned δ) or less, with the exception of very few areas at the coil ends.
[0067] Therefore, it was concluded that for the coil described above, final annealing at an atmosphere switching temperature of 800°C is optimal. In other words, based on the results of this experiment, the atmosphere switching temperature setting (H) can be set to 800°C. Note that the final annealing conditions, except for the atmosphere switching temperature, are identical to those described above.
[0068] Then, the annealing separator is removed, and a coating agent based on phosphate is applied, which also serves as a flattening annealing process for sintering. The appearance of the film is evaluated using a surface inspection device, and a uniform appearance without uneven color or spot-like film defects is considered acceptable. The resulting film pass rate is as high as 99.7%. It should be noted that in this evaluation, since the insulating film (here, a glass film based on phosphate) is transparent, it can be considered that the film pass rate evaluates the characteristics of the base film.
[0069] As described above, the method of the present invention was applied to each coil under conditions where the atmosphere switching temperature was varied as described above, and compared to conditions where the atmosphere switching temperature was held constant at 800°C. The film appearances were then compared. The results showed that the film yield rate reached a high of 99.7% when the atmosphere switching temperature was adjusted for each coil. In contrast, the film yield rate was only 91.3% when the switching temperature was held constant at 800°C. This indicates that optimizing the switching temperature for each coil significantly improves the film yield rate.
[0070] Here, the film pass rate refers to the ratio of the qualified portion with uniform appearance in the surface area of the coil. For example, the surface area of the coil to be evaluated is 100,000 m 2 , the surface area of the qualified part is 90000m 2 The pass rate was 90.0%.
[0071] That is, conventionally, the atmosphere switching temperature in the final annealing was managed using a representative point. Therefore, although the film properties at the representative point were good, there were defective portions throughout the entire length and width of the coil, making it difficult to obtain good quality at a high yield.
[0072] In contrast, according to the present invention, the final annealing is performed at the set value (H) of the above-mentioned control item (for example, the atmosphere switching temperature of the above-mentioned final annealing) so that the range of good film properties is the range with the largest area of the steel sheet wound into the coil (hereinafter also referred to as the coil area), thereby achieving the effect of significantly improving the manufacturing yield.
[0073] In the present application, as a step for maximizing the range of the above film properties in terms of the area of the coil, a plurality of appropriate items among various items conventionally used as control items are selected in advance together with set candidate values (hO, hi, h2,...), and a set value (H) is most effectively obtained from the set candidate values (hO, hi, h2,...) by the relationship of f(M) and δ as described above.
[0074] In addition, the following step can be cited: in a laboratory, a base film is evaluated by changing an enrichment component and a control item as an object, a relationship of the amount of the enrichment component and the control item for which the properties of the base film are optimal is formulated, an appropriate control item for each region is determined from the amount of the enrichment component, a set candidate value of the control item for which the number of regions is largest is selected from a histogram of the set candidate values of the control item with respect to the number of regions, and the selected value is adopted as a set value (H) of the control item for final annealing. Note that, as the final annealing, there are a case where final annealing including homogenizing heat treatment is performed or a case where homogenizing heat treatment and final annealing are performed separately, but both are simply referred to as final annealing.
[0075] Alternatively, a relationship for which a good film is obtained can be obtained from the value of the enrichment component and the value of the control item in actual production, and the same processing can be performed.
[0076] These relationships are quantified in advance in a laboratory or data analysis of a product quality, and the set value (H) of the condition of the control item for final annealing is determined in consideration of these relationships. Note that, as the control item, in addition to the above-mentioned atmosphere switching temperature, any one or two or more of the temperature rising rate of 950 to 1100°C for final annealing, the homogenizing heat treatment time, and the homogenizing heat treatment temperature can be used. In the present application, the control item refers to one or two or more items appropriately selected from the above-mentioned four items.
[0077] The steps of the present application are generally described as follows.
[0078] First, for each region of a steel sheet divided in a certain area in the width direction and the length direction of the sheet, the concentration of an enrichment component in an internal oxidation film of decarburization annealing is derived, for example, by monitoring or calculation (the concentration of the enrichment component is set to M).
[0079] Next, the influence of a control item for final annealing on the properties of a base film with respect to the above-mentioned M is evaluated.
[0080] Based on the evaluation result, a relationship f(M) of the above-mentioned M and the above-mentioned control item for which the properties of the base film are good is obtained, and an allowable value ± δ for which the properties of the base film are good is obtained.
[0081] Further, the plurality of set-up candidate values (h0, h1, h2...) will be selected in the same manner as the above step.
[0082] Further, for the control item of the final annealing, for each region divided by a certain area in the width direction and the length direction of the steel sheet, the distribution of the actual (or calculated) control item on the steel sheet given by setting each of the plurality of set-up candidate values (h0, h1, h2...) is found, for example, by monitoring or calculation.
[0083] Note that the above certain area in the present application is the finer the better for more detailed correspondence, but due to the resolution of the monitoring device, the simulation accuracy of the final annealing, even if it is too fine, sometimes no effective data can be obtained. Therefore, the range of the width direction: 1 to 400 mm pitch, the length direction: 5 to 200 mm pitch is practical and preferable.
[0084] Using the above results, the set-up value (H) of the control item that becomes the largest total area of the region within the range of the above allowable value ± δ is selected from the above set-up candidate values (h0, h1, h2...) in the following steps.
[0085] That is, the enriched component in the internal oxidation film as the above monitoring index [enriched component index (M)] is as described above. Further, in conjunction with the monitoring of the concentration of this enriched component of the coiled steel sheet after the decarburization annealing, the optimum value of the control item of the final annealing depending on the position of the coiled steel sheet is derived as described above.
[0086] Next, using the above function f(M), the above set-up candidate values h0, h1, h2... and the above allowable range ± δ, the set-up value (H) is set from the set-up candidate values (h0, h1, h2...) of the control item in the above method in such a manner that the total area of the region that becomes |f(M) - h0| ≤ δ is the largest on the entire surface of the coiled steel sheet.
[0087] As described above, the control item can use any one or two or more of the temperature rising rate of the final annealing between 950 and 1100°C, the atmosphere switching temperature, the homogenization heat treatment time and the homogenization treatment temperature. This is because the optimum range of these items easily changes depending on the quality of the decarburization annealed steel sheet, in particular.
[0088] Note that for the relationship f(M) of the control item and the monitoring index (concentration M) and δ, it can be found in advance in the laboratory or by data analysis on the results of the actual machine.
[0089] The method for determining f(M) is not particularly limited. Specifically, when using laboratory experimental results, the enriched component of the decarburized annealed sheet can be calculated using a fluorescent X-ray analyzer, FTIR, or the like, and the final annealing conditions can be varied to obtain product sheets. The film appearance of the product sheets can then be observed to determine a regression equation based on the results. Alternatively, the product sheets can be subjected to an adhesion test in accordance with JIS C2550 and the film adhesion can be evaluated under various final annealing conditions to determine a regression equation. When using data analysis, the strength of the enriched component of the decarburized annealed sheet can be compared with the final annealing conditions, and the film adhesion pass rate can be determined using the aforementioned film pass rate criteria.
[0090] In the above-mentioned method for determining δ, when laboratory experimental results are used, the same equipment as used for the above-mentioned method for determining f(M) is used as the test result. For example, in the case of film appearance, visual acceptance is used as the basis, or in the case of a JIS C2550 adhesion test, the user-defined test acceptance value is used as the basis. The parameters are varied by approximately 20 to determine the range within which the base film is good. This range is then halved to determine δ. On the other hand, when data analysis is used, the same equipment and analysis tools as used for the above-mentioned method for determining f(M) are used, along with the above-mentioned laboratory acceptance criteria for the film acceptance rate. The parameters are also varied by approximately 20 to determine the range within which the base film is good. This range is then halved to determine δ. It should be noted that the formulation is not limited to linear regression; various machine learning algorithms such as SVM, random forest, and principal component analysis can also be used to set optimal values and ranges.
[0091] Next, other requirements of the present invention will be described.
[0092] The steel billet (slab) used to produce the grain-oriented electrical steel sheet subjected to the final annealing according to the conditions determined in the present invention may be a steel billet used in the production of conventionally known grain-oriented electrical steel sheets. The composition of the steel billet is specifically described below.
[0093] C: 0.01-0.10 mass%
[0094] If the C content is less than 0.01% by mass, the grain boundary strengthening effect due to C disappears, causing cracks in the slab and other defects that affect manufacturing. On the other hand, if the C content exceeds 0.10% by mass, it is difficult to reduce it to 0.004% by mass or less, which does not cause magnetic aging during decarburization annealing. Therefore, the C content is preferably within the range of 0.01% to 0.10% by mass. More preferably, the lower limit is 0.02% by mass and the upper limit is 0.08% by mass.
[0095] Si: 2.5-4.5 mass%
[0096] Si is an element necessary for increasing the resistivity of steel and reducing iron loss. This effect is insufficient when the content is less than 2.5% by mass. On the other hand, if the content exceeds 4.5% by mass, workability decreases, making rolling difficult. Therefore, the Si content is preferably within the range of 2.5 to 4.5% by mass. A more preferred lower limit is 2.8% by mass, and an upper limit is 3.7% by mass.
[0097] Mn: 0.01-0.50 mass%
[0098] Mn is an element necessary for improving the hot workability of steel. Less than 0.01% by mass will not provide sufficient effects. On the other hand, exceeding 0.50% by mass reduces the magnetic flux density of the finished sheet. Therefore, the Mn content is preferably within the range of 0.01% to 0.50% by mass. A more preferred lower limit is 0.02% by mass, and an upper limit is 0.20% by mass.
[0099] Regarding the components other than the above-mentioned C, Si, and Mn, the amount of the components to cause secondary recrystallization is different depending on whether the formulation is used or not.
[0100] First, to induce secondary recrystallization, when using inhibitors, for example, AlN-based inhibitors, Al and N are preferably contained in the ranges of 0.01-0.04 mass% Al and 0.003-0.015 mass% N, respectively. Furthermore, when using MnS·MnSe-based inhibitors, it is preferred to contain the aforementioned amounts of Mn, along with one or both of 0.002-0.03 mass% S and 0.003-0.03 mass% Se. If these addition amounts are below the aforementioned lower limits, the inhibitor effect cannot be fully achieved. On the other hand, if the aforementioned upper limits are exceeded, the inhibitor remains undissolved during slab heating, resulting in a decrease in magnetic properties. It should be noted that AlN-based and MnS·MnSe-based inhibitors can be used in combination.
[0101] In contrast, in order to cause secondary recrystallization, when no inhibitor is used, it is preferred to use a steel billet in which the contents of the inhibitor-forming components, i.e., Al, N, S, and Se, are reduced as much as possible to less than 0.01 mass% Al, less than 0.005 mass% N, less than 0.005 mass% S, and less than 0.005 mass% Se.
[0102] In the steel material used in the present invention, the remainder other than the above components is essentially Fe and inevitable impurities. In addition, for the purpose of improving magnetic properties, in addition to the above components, it may also contain appropriately selected from Ni: 0.010-1.50 mass%, Cr: 0.01-0.50 mass%, Cu: 0.01-0.50 mass%, P: 0.005-0.50 mass%, Sb: 0.005-0.50 mass%, Sn: 0.005-0.50 mass%, Bi: 0.005-0.5 0 mass%, Mo: 0.005-0.100 mass%, B: 0.0002-0.0025 mass%, Te: 0.0005-0.0100 mass%, Nb: 0.0010-0.0100 mass%, V: 0.001-0.010 mass%, Ti: 0.001-0.010 mass% and Ta: 0.001-0.010 mass%.
[0103] Next, a method for producing a grain-oriented electrical steel sheet including final annealing using the conditions determined by the present invention will be described.
[0104] The slab to be used as the steel billet for the above-mentioned manufacturing method can be manufactured by smelting steel having a composition suitable for the above-mentioned present invention in a refining process using a conventional method, and then using a known ingot-blowing rolling method or a continuous casting method. In addition, a thin slab with a thickness of less than 100 mm can be directly produced by a casting method.
[0105] The slab is heated to a predetermined temperature according to a conventional method, for example, to a temperature of about 1400°C, specifically 1300-1450°C, when containing inhibitor-forming components, to dissolve the inhibitor-forming components into the steel, and then hot-rolled to produce a hot-rolled plate.
[0106] On the other hand, when the inhibitor-forming component is not contained, the steel sheet is heated to a temperature of 1250°C or lower and then hot-rolled to produce a hot-rolled sheet. Note that when the inhibitor-forming component is not contained, the steel sheet may be hot-rolled immediately after casting without heating.
[0107] In the case of thin cast slabs, hot rolling can be performed, or hot rolling can be omitted and the hot rolled sheet can be annealed in the next step, or the hot rolled sheet can be annealed without annealing. The hot rolling conditions can be conventional and are not particularly limited.
[0108] The hot-rolled sheet after hot rolling is subjected to hot-rolled sheet annealing as needed. The soaking temperature for the hot-rolled sheet annealing is preferably in the range of 800-1150°C in order to obtain good magnetic properties. If the soaking temperature is less than 800°C, the effect of the hot-rolled sheet annealing is insufficient, the banded structure formed by hot rolling remains, and a primary recrystallization structure with regular grains cannot be obtained, which may hinder the development of secondary recrystallization. On the other hand, if the soaking temperature exceeds 1150°C, the grain size after hot-rolled sheet annealing becomes too coarse, and it is still difficult to obtain a primary recrystallization structure with regular grains.
[0109] The hot rolled sheet after hot rolling or hot rolled sheet annealing and the thin cast sheet are made into cold rolled sheet of the final sheet thickness by cold rolling once or by cold rolling twice or more with intermediate annealing. The annealing temperature of the intermediate annealing is preferably in the range of 900 to 1200°C. If the annealing temperature is less than 900°C, the recrystallized grains after the intermediate annealing become finer, and the Goss nuclei of the primary recrystallization structure decrease, which may reduce the magnetic properties of the product sheet. On the other hand, if the annealing temperature exceeds 1200°C, the grains become too coarse, similar to the annealing of the hot rolled sheet, making it difficult to obtain a primary recrystallization structure with regular grains.
[0110] In addition, for cold rolling to the final sheet thickness (final cold rolling), it is preferable to adopt warm rolling in which the steel sheet temperature is raised to 100-300°C, or to perform inter-pass aging treatment at 100-300°C one or more times during cold rolling. This improves the primary recrystallization texture and further enhances the magnetic properties.
[0111] The cold-rolled sheet to be made into the final sheet thickness is subjected to decarburization annealing which also serves as primary recrystallization annealing. Here, the heating process of the above-mentioned decarburization annealing is preferably rapidly heated to a temperature between 500 and 700°C at a heating rate of more than 50°C / s. As a result, the secondary recrystallized grains are refined and the iron loss characteristics are improved. In addition, the soaking temperature for decarburization annealing is preferably 780 to 950°C, and the soaking time is preferably in the range of 80 to 200 seconds. When the soaking temperature is lower than 780°C or the soaking time is shorter than 80 seconds, insufficient decarburization or insufficient primary grain growth occurs. On the other hand, when the soaking temperature exceeds 950°C or the soaking time exceeds 200 seconds, the grain growth of the primary recrystallized grains proceeds excessively. A more preferred soaking temperature is 800 to 930°C, and the soaking time is in the range of 90 to 150 seconds.
[0112] The atmosphere during soaking for decarburization annealing is preferably a wet hydrogen atmosphere with the dew point and oxygen potential (PH2O / PH2) adjusted to a range of 0.3 to 0.6. If the PH2O / PH2 is less than 0.3, decarburization is insufficient. On the other hand, if it exceeds 0.6, FeO is likely to form on the steel sheet surface, degrading the film properties. A range of 0.4 to 0.55 is more preferred. The oxygen potential (PH2O / PH2) of the atmosphere during heating for decarburization annealing does not need to be the same as that during soaking; it can be controlled separately.
[0113] Furthermore, the soaking atmosphere does not need to be constant. For example, the soaking process can be divided into two stages, with the oxygen potential PH2O / PH2 in the latter stage set to a reducing atmosphere of 0.2 or less. This improves the morphology of the internal oxide film formed on the steel sheet surface, beneficially contributing to improvements in magnetic and coating properties. A more preferred PH2O / PH2 ratio in the latter stage is 0.15 or less. While the time ratio between the first and second stages is not particularly limited, the latter stage preferably accounts for approximately 25% or less of the time in the former stage.
[0114] Here, in the present invention, it is important to monitor a specific index (enrichment component index (M)) of the internal oxide film of the decarburized annealed sheet in the width direction and the length direction. As a specific index (enrichment component index (M)) of the internal oxide film, for example, the detection intensity of elements such as O, Si, Al, Mn, and P on the steel sheet surface by X-rays, gamma rays, infrared spectroscopy, etc., i.e., the enrichment degree (M) of these elements, or the detection intensity ratio of the surface layer of FeO, Fe2SiO4, and SiO2 products, i.e., the enrichment degree (M) of these products, can be used.
[0115] The above-mentioned elements can be detected using various analysis methods such as X-rays, gamma rays, and infrared spectroscopy. In addition, when fluorescent X-ray analysis is used, the analysis conditions are generally about 10 to 60 kV and 1 to 30 mA, but there are no special restrictions. Generally speaking, if the voltage is increased, more internal information of the steel plate can be obtained. It should be noted that the detection of the above-mentioned elements can also be combined using these measured values. Alternatively, when sufficient data is available and the change in intensity at a specific location can be predicted from the characteristics of the device, the concentration distribution can be derived from the temperature and atmosphere conditions of the decarburization annealing through numerical simulation.
[0116] The above-mentioned on-line analysis is preferably performed between after decarburization annealing and before the application of the annealing separator. However, if the annealing separator does not contain the element to be measured, it may be performed after the application.
[0117] It should be noted that the above-mentioned online analysis is preferably performed on the surface and back of the steel plate over the total length and total width of the coil, but when the extent of the difference in a specific part (such as the difference between the surface and back of the steel plate) is known in advance from past data or characteristics on the equipment, analysis of other parts (such as only the surface (front) surface) may also be performed.
[0118] After the decarburization annealing, a slurry of an annealing separator composed primarily of MgO is applied to the surface of the steel sheet and then dried. The annealing separator contains 50% by mass or more of MgO as its main component. If the MgO content is less than 50% by mass, the main component for film formation is insufficient, resulting in a poorly formed film. Furthermore, the MgO content is preferably 70% by mass or more.
[0119] In addition, the annealing separator with the above-mentioned MgO as the main component can be appropriately added with conventionally known additives, such as compounds of Ti, Na, Al, Sb, Ca, etc. In this case, the total content of the above-mentioned compounds is less than 50% by mass. If the content of the compound is 50% by mass or more, the content of MgO is less than 50% by mass, resulting in poor formation of the forsterite film. More preferably, the total content of the compound is 30% by mass or less. In addition, the coating amount of the annealing separator on the steel plate surface, the hydration temperature, and the time are within the known ranges and are not particularly limited.
[0120] The steel sheet coated with the annealing separator is then heated and held in an annealing furnace in an upright coiled state (standing axially in the coil), inducing secondary recrystallization and then undergoing a purification treatment, leading to a final annealing. To induce secondary recrystallization, this final annealing is preferably performed by heating to a temperature of 1100°C or higher and then holding. To complete secondary recrystallization, the temperature is preferably increased at a rate of 2 to 50°C / h within the 700-1100°C temperature range when performing secondary recrystallization during heating. Furthermore, when performing secondary recrystallization during holding, the temperature is preferably held within the above holding temperature range for at least 25 hours. The atmosphere during this process is always an inert atmosphere such as N2 or Ar at a temperature below 500°C. Furthermore, at any temperature between 500°C and 1100°C, the inert atmosphere is switched to an atmosphere containing 5% or more H2. A temperature below 500°C poses an explosion risk. On the other hand, a temperature above 1100°C increases the duration of the inert gas flow, resulting in film degradation.
[0121] In the above-mentioned final annealing, after inducing secondary recrystallization, in order to form a forsterite film (base film) and remove impurities contained in the steel sheet, it is preferable to carry out a purification treatment at a temperature of 1120-1250°C for 2-50 hours. If the temperature of the above-mentioned purification treatment is less than 1120°C or the holding time is less than 2 hours, the purification is insufficient. On the other hand, if the temperature of the purification treatment exceeds 1250°C or the holding time exceeds 50 hours, the coil bends and deforms, resulting in poor shape and reduced yield. More preferably, the lower limit of the temperature of the above-mentioned purification treatment is 1150°C. On the other hand, the upper limit of the temperature of the above-mentioned purification treatment is 1230°C. Furthermore, more preferably, the lower limit of the holding time of the above-mentioned purification treatment is 3 hours. On the other hand, the upper limit of the holding time of the above-mentioned purification treatment is 40 hours.
[0122] It should be noted that in the present invention, a preliminary heat treatment at a predetermined temperature and time may be performed before the final annealing to achieve a homogenization heat treatment that evens out the element concentrations on the surface and back of the steel sheet. This homogenization heat treatment is preferably performed at a temperature of 800-950°C for 5-200 hours. If the temperature is less than 800°C or the treatment time is less than 5 hours, the aforementioned effects cannot be fully achieved. On the other hand, if the temperature exceeds 950°C or the treatment time exceeds 200 hours, the activity of MgO is lost, degrading the film properties.
[0123] Furthermore, the homogenization heat treatment can be performed separately from the final annealing, or it can be incorporated into the first half of the final annealing and performed after the homogenization heat treatment. Furthermore, since the conditions of the homogenization heat treatment overlap with the temperature range in which secondary recrystallization occurs, the process of causing secondary recrystallization during the final annealing can be omitted when the homogenization heat treatment is performed, whether separately or incorporated.
[0124] It should be noted that in the present invention, the conditions (control items) of the final annealing in the final annealing may be at least one condition selected from the above-mentioned conditions of the final annealing, such as the conditions of the homogenization heat treatment, or a plurality of conditions may be selected. Furthermore, in the present invention, even when the homogenization heat treatment is performed separately from the final annealing, the conditions of the homogenization heat treatment are considered to be one of the conditions of the final annealing.
[0125] When the homogenization heat treatment and final annealing are performed separately, the heating rate from room temperature to the purification treatment temperature is preferably in the range of an average of 5 to 50°C / h. It should be noted that this heating rate is more preferably an average of 8°C / h or higher. On the other hand, it is more preferably an average of 30°C / h or lower. Furthermore, when the homogenization heat treatment is incorporated into the final annealing, it is preferred that the final annealing following the homogenization heat treatment be performed from the homogenization heat treatment temperature to the purification treatment temperature at an average heating rate of 5 to 50°C / h. It should be noted that this average heating rate is more preferably 8°C / h or higher. On the other hand, it is more preferably 30°C / h or lower.
[0126] Since the final annealing is performed in a coiled state, heat diffusion takes time, resulting in a temperature difference within the coil, which may be 500° C. or more depending on the situation.
[0127] Therefore, even if the conditions for the final annealing are set according to the temperature history described above, the temperature difference varies greatly depending on the position in the coil. Therefore, in the present invention, it is necessary to understand the temperature (set value) of each position (region) in the coil through actual measurement and simulation.
[0128] It should be noted that the simulation method can use any of the various proposed temperature simulation methods, such as the finite difference method and the finite element method. Furthermore, when performing this simulation, it is desirable to install thermocouples or other temperature measuring devices at various locations on the coil to measure the temperature and incorporate this into the calculation to further improve the accuracy of the calculation.
[0129] Using this method, the monitoring results (enrichment component index (M)) of the decarburized annealed sheet are matched with the control parameters of the final annealing as described above. As the matched control parameters of the final annealing, one or more of the following can be appropriately selected: the heating rate, the switching temperature to the H2-containing atmosphere, the homogenization heat treatment time, and the homogenization heat treatment temperature.
[0130] As is well known, the optimal conditions for final annealing vary depending on the quality of the internal oxide film formed by decarburization annealing. For example, in decarburization-annealed sheets where a large amount of Fe oxides are generated in the internal oxide film, these Fe oxides decompose during final annealing, generating oxygen that adversely affects the film. Therefore, lowering the temperature at which H2 is introduced into the annealing atmosphere is effective in reducing the Fe oxides before they decompose. In contrast, under conditions where almost no Fe oxides are generated, the amount of internal oxide film is small, and the amount of forsterite raw material is low. Therefore, it is necessary to increase the temperature at which H2 is introduced during final annealing to replenish oxygen to the film raw material through oxidation during final annealing.
[0131] If this relationship is compared with the indicators described so far, when the index (M) of the enriched component enriched on the surface of the decarburized annealed sheet, that is, the concentration (intensity) of any one of O, Mn, Al, and P, or the concentration (intensity ratio) of any one of FeO and Fe2SiO4 that generate oxides increases, film formation is likely to occur. Therefore, it is effective to change the conditions of the final annealing control items, that is, to reduce the heating rate during the final annealing, reduce the H2-containing atmosphere switching temperature, or shorten the homogenization heat treatment time.
[0132] In addition, when the Si content of the decarburized annealed sheet increases, film formation becomes relatively difficult to occur. Therefore, increasing the temperature rise rate during the final annealing, increasing the H2-containing atmosphere switching temperature, or extending the homogenization heat treatment time are effective.
[0133] After the final annealing, the steel sheet is preferably subjected to flattening annealing to correct its shape after being washed with water, brushed, or pickled to remove unreacted annealing separators adhering to the surface of the steel sheet. This is because the final annealing is performed while the steel sheet is wound into a coil, and this is done to prevent deterioration of the magnetic properties due to coil marks.
[0134] When laminating product sheets using grain-oriented electrical steel sheets, it is preferable to have an insulating coating on the surface of the steel sheets. In particular, when iron loss characteristics are important, it is preferable to use a tension-applying coating that applies tension to the steel sheets as the insulating coating. Application of this insulating coating can be performed during the flattening annealing described above, or in a process before or after the flattening annealing.
[0135] In order to further reduce iron loss, a magnetic domain refinement treatment may be performed. Conventional methods for refining magnetic domains may be used, such as etching grooves on the surface of a cold-rolled steel sheet to its final thickness, or irradiating the surface of a finished steel sheet with laser or plasma to introduce linear or point-shaped thermal strain or impact strain.
[0136] Example 1
[0137] A steel containing 0.05 mass% C, 3.6 mass% Si, 0.08 mass% Mn, 0.022 mass% Al, 0.02 mass% Se, 0.07 mass% Sb, with the remainder consisting of Fe and inevitable impurities, was smelted and formed into a steel billet (slab) by a continuous casting method. The slab was then heated to 1390°C and hot rolled to form a hot-rolled plate with a thickness of 2.6 mm. The hot-rolled plate was annealed at 1000°C for 60 seconds, followed by a single cold rolling to form an intermediate plate with a thickness of 1.8 mm. After an intermediate annealing at 1100°C for 80 seconds, a secondary cold rolling was performed to form a cold-rolled plate with a final thickness of 0.23 mm.
[0138] Next, the cold-rolled sheet was passed through a horizontal continuous annealing furnace, where the temperature was increased between 500°C and 700°C at a heating rate of 500°C / s and held at 800°C for 150 seconds, performing a decarburization annealing that also served as a primary recrystallization annealing. During this decarburization annealing, an atmosphere of H2:N2 = 50:50 vol% was supplied from above and below the annealing furnace. After the decarburization annealing, the intensity ratios of Fe2SiO4, SiO2, and FeO were measured online using an infrared spectrometer before coiling. The measured values were digitized as (Fe2SiO4 intensity ratio) / (sum of the intensity ratios of SiO2, Fe2SiO4, and FeO). Measurements were taken at intervals of 50 mm across the sheet width and 50 m along its length to create a graph.
[0139] Furthermore, a powder primarily composed of MgO and containing 6% by mass of titanium oxide and 3% by mass of strontium sulfate was slurried in water to form an annealing separator. This annealing separator was applied to the surface of the steel sheet, dried, and wound into a coil for final annealing. The final annealing was then performed by heating in an N2 atmosphere at a heating rate of 10°C / h between room temperature and 900°C, followed by a homogenization heat treatment at 900°C for 12 to 60 hours. Subsequently, secondary recrystallization was completed by heating in an H2 atmosphere at a heating rate of 10°C / h between 900°C and 950°C and then between 950°C and 1100°C. The steel was then heated in an H2 atmosphere at a heating rate of 10°C / h between 1100°C and 1200°C, followed by a purification treatment held at 1200°C for 10 hours.
[0140] Here, when setting the time for the homogenization heat treatment (homogenization heat treatment time), based on analysis of data on the Fe₂SiO₄ intensity ratio in the coil and the homogenization heat treatment time implemented to date, it was confirmed that a good coating is obtained if the difference ±δ between the homogenization heat treatment time and the time (optimum value) obtained from the following equation (1) is within ±20 hours. The following equation (1) represents the function f(M).
[0141] 100-150×(Fe2SiO4 intensity ratio)〔h〕···(1)
[0142] Based on this, candidate setting values (h0, h1, h2, ...) for the homogenization heat treatment time at each coil position (each region of the coil) at the end of the homogenization heat treatment are selected from the temperature simulation within the coil. From these candidate setting values h0, h1, h2, ..., the condition in which the total area of the region where the difference ±δ from the (optimal value) obtained by the above formula (1) is within ±20 hours is maximized is set as the setting value H. After the homogenization heat treatment temperature is set to 900°C, the homogenization heat treatment time is set to the above setting value H for each coil based on a thermocouple installed on the hearth in contact with the winding portion of the coil.
[0143] Then, after removing the annealing flux remaining in the steel sheet, a coating agent is applied, and further, sintering is performed to perform a planarization anneal, and an insulating film (a glass film mainly composed of phosphates) is formed on the surface of the steel sheet.
[0144] When manufacturing 10 of the above-described coils, homogenization heat treatment was performed on each of the coils according to the above-described steps with the set value H set. The appearance of the film of the 10 coils thus obtained was visually determined by a surface inspection device. Note that the pass / fail determination was based on the criteria of Experiment 1 described above.
[0145] As a result of this determination, a high value of 99.8% was obtained as the film pass rate on average for the 10 coils. In contrast, when homogenization heat treatment was performed at 900°C for all of the 10 coils without according to the present application, and the value of the average of the entire steel sheet in which the intensity ratio of Fe2SiO4in the above-described formula (1) was substituted: 50 hours, the film pass rate was 96.3% on average for the 10 coils.
[0146] Example 2
[0147] A steel containing C: 0.04 mass%, Si: 3.2 mass%, Mn: 0.08 mass%, Al: 0.006 mass%, Sn: 0.04 mass%, and the remainder composed of Fe and inevitable impurities was melted, and after a slab material (slab) was manufactured using a continuous casting method, the slab was heated to 1260°C, and hot rolling was performed to manufacture a hot-rolled sheet having a sheet thickness of 2.8 mm. After annealing of the hot-rolled sheet at 1100°C for 60 seconds was performed, cold rolling was performed to manufacture a cold-rolled sheet having a final sheet thickness of 0.23 mm.
[0148] Next, decarburization annealing that also served as primary recrystallization annealing was performed in a horizontal (horizontal) continuous annealing furnace by raising the temperature at a temperature increasing rate of 300°C / s between 500°C and 700°C in the heating process, maintaining at 820°C for 120 seconds, and further maintaining at 850°C for 30 seconds. In the decarburization annealing, an atmosphere gas of H2:N2= 50:50 in vol% was supplied from above and below the annealing furnace. After the decarburization annealing was completed, the intensity (concentration) distribution of O, Si, Al, Mn, and P was measured on-line using a fluorescent X-ray device before the sheet was wound into a coil. The measurement values were measured at intervals of 50 mm in the sheet width direction and at intervals of 50 m in the length direction to produce a graph.
[0149] Furthermore, a powder primarily composed of MgO and containing 4% by mass of titanium oxide and 2% by mass of ammonium sulfate was slurried in water to form an annealing separator. This annealing separator was applied to the surface of the steel sheet, dried, and wound into a coil for final annealing. The final annealing was then performed by heating in an N2 atmosphere at a heating rate of 10°C / h between room temperature and 950°C. In an H2 atmosphere, the heating rate was varied between 950°C and 1100°C. Furthermore, in an H2 atmosphere, the heating rate was increased by 10°C / h between 1100°C and 1200°C, followed by a purification treatment at 1200°C for 10 hours.
[0150] Here, in the step of setting the heating rate between 950°C and 1100°C, the optimal heating rate (optimal value) is determined for each coil based on the data analysis of the strength of each element in the coil (the enrichment component index (M)) and the heating rate performed up to that point. Furthermore, the heating rate (candidate setting values h0, h1, h2, etc.) is determined for each coil location (each region of the coil) based on the temperature simulation within the coil. The setting value H is then determined as the setting candidate value with the largest area within the specified heating rate (δ) between the optimal heating rate (optimal value) obtained from the strength of each element and the heating rate at each location (each region of the coil) from the temperature simulation.
[0151] Specifically, when the peak intensities of O, Si, Al, Mn, and P are set to P(O), P(Si), P(Al), P(Mn), and P(P), respectively, the condition is set so that the total area of the region where the difference ±δ from the (optimal value) obtained by the following formula (2) is ±4°C / h is the largest.
[0152] f(O, Si, Al, Mn, P)=8.8×P(O)-1.1×P(Si)-11×P(Al)-13×P(Mn)+6.0×P(P)+88(℃ / h)···(2)
[0153] The heating rate is set based on the measurement of a thermocouple installed on the hearth in contact with the coiled portion of the coil. The above formula (2) is a function f(M).
[0154] Then, the annealing separator remaining in the steel sheet is removed, a coating agent is applied, and further flattening annealing is performed which also serves as sintering to form an insulating film (a glass film mainly composed of phosphate) on the surface of the steel sheet.
[0155] When producing the coils described above 10 times, the temperature of each coil was raised between 950°C and 1100°C according to the above procedure, with the set value H set. The coating appearance of the ten coils obtained in this manner was visually inspected using a surface inspection device. The acceptance criteria of Experiment 1 were used.
[0156] When the present invention was used to determine the maximum heating rate (H) for each coil, with the total area within the range (region) where |f(M) - h0| ≤ δ, across the entire coil surface, the average of the ten coils yielded an extremely high coating pass rate of 99.94%. In contrast, when the present invention was not used and the heating rate was uniformly set at 10°C / h (the value obtained by substituting the average value of the strength values into the above formula (2)) for all ten coils, the average coating pass rate for the ten coils was 96.5%.
Claims
1. A method for determining final annealing conditions for a grain-oriented electrical steel sheet, wherein a steel billet for the grain-oriented electrical steel sheet is hot-rolled, then subjected to one cold rolling step or two or more cold rolling steps with intermediate annealing, further subjected to a decarburization annealing step also serving as a primary recrystallization annealing step, coated with an annealing separator, wound into a coil, subjected to a final annealing step to form a base film, and subsequently subjected to a flattening annealing step to produce a product sheet. When determining the conditions for the final annealing, perform the following operations: 1) when the decarburization annealed steel sheet is divided into a plurality of regions in the length direction and the width direction, information on a component enrichment index (M) in the internal oxide film of the decarburization annealed steel sheet is obtained for each of the regions; 2) before determining the final annealing conditions, deriving an optimal function f(M) of the final annealing control item with respect to the enrichment component index (M) based on an evaluation result of the influence of the final annealing control item on the characteristics of the base film for the enrichment component, 3) obtaining information on the entire steel plate regarding the distribution of the control item for each of the regions with respect to a plurality of candidate values for the setting value (H) of the control item for the finish annealing, 4) determining whether the distribution of the control items for each of the regions is within a predetermined tolerance range (±δ) relative to f(M), and selecting a setting value (H) for the control item that maximizes the total area of the regions within the tolerance range from the plurality of candidate values; The enrichment component index (M) is set to any one or more of the O concentration, Si concentration, Al concentration, Mn concentration, P concentration, Fe2SiO4 intensity ratio, SiO2 intensity ratio and FeO intensity ratio on the steel plate surface, The control parameters of the final annealing are any one or two or more of the heating rate between 950° C. and 1100° C., the atmosphere switching temperature, the homogenization heat treatment time, and the homogenization heat treatment temperature of the final annealing.
2. A method for manufacturing a grain-oriented electrical steel sheet, characterized in that: The method for determining the final annealing conditions according to claim 1 is used.
Citation Information
Patent Citations
Finish annealing method for grain oriented electrical steel sheet
JP1996209248A
Production of grain oriented silicon steel sheet with extremely high magnetic flux density
JP1997003541A
Production of ultralow core loss ultrahigh magnetic flux density grain-orineted silicon steel strip
JP1997111346A
Method for controlling atmosphere for voided material and method for finish-annealing grain oriented magnetic steel sheet
JP2000239736A
Method for producing grain oriented silicon steel excellent in coil shape
JP2001303137A